If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-87) + x = -25 -87 + x = -25 Solving -87 + x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '87' to each side of the equation. -87 + 87 + x = -25 + 87 Combine like terms: -87 + 87 = 0 0 + x = -25 + 87 x = -25 + 87 Combine like terms: -25 + 87 = 62 x = 62 Simplifying x = 62
| 0=8v-8v | | 2(3k+7)+12(2+k)=-16 | | -3x+6x=-12+4x-5x | | 0.06/18 | | -16q+7=-16q-2 | | 38+x=82 | | 11a=24+8a | | -2-4-3b=-6-10b | | 7x+6=7(x-7) | | -10c-10=2-8c | | -5n-8=1-8n | | 9f=10+9f | | 6n-8(n+5)=-70 | | -4-8n+8n=n+3 | | -7m+m-4=-6m+5 | | 6(x+1)/5=5x-5 | | 7x+5=2x+1 | | -x+41+8x-9=-3 | | 0.40x+0.45(20)=0.20(35) | | -10t=-10t+9 | | 4(3y-2)/7=3y-5 | | 7(x-4)=4x-16 | | 1.6x=.8x | | 2/7x+3/7=-1/7 | | 5-7x=50-42x | | 5+9k=-k-5 | | -15-5m=-6m+6m | | 2-5y=5(1-2y) | | 5a+2(a-3)=15 | | 8x^2+10-72=0 | | 4x-8x-8=-3x+4-4 | | -4(4x+6)=16 |